Identification of Student Misconception using a Three-tier Diagnostic Test on Colloid - Ratman Ratman; Nurafni Nurafni; Kasmudin Mustapa; Minarni R. Jura; Nurida Nurida; Nurasiah Nurasiah (Jurnal Akademika Kimia, 2022)
This study aims to identify the percentage of misconceptions that occur in students on colloid material in class XI MIPA 2 SMA Negeri 1 Dampal Selatan Kabupaten Tolitoli is based on the results of a three-level diagnostic test and shows which subconcepts have the highest and lowest conceptions. The instrument used in this study was a three-level multiple choice diagnostic test. The results showed students' misconceptions about colloid material in class XI MIPA 2, which was 65.51%. The results of this study indicate that the level of students' misconceptions about colloidal material is a high category.